CLINICAL CASE OF EXTRAUTERINE PREGNANCY, LOCATED IN RUDIMENTAL UTERINE HORN AT 21-22 WEEK OF GESTATION - S. Zh. Danelyan; T. K. Gogichaev; N. M. Gulyaeva; E. M. Dzhobava; Yu. E. Dobrokhotova (Акушерство, гинекология и репродукция)
In article the question is a case of extrauterine pregnancy in term of 21-22 weeks in the rudimentary horn of a uterus in term of 21-22 weeks interrupted because of break of a horn with an intrabelly bleeding. The operation and tactical approaches to conducting the given case are described.